Encyclopedia of Life Sciences 2015
DOI: 10.1002/9780470015902.a0020477.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Crop–Weed Competition

Abstract: Competition from weeds is the most important of all biological factors that reduce agricultural crop yield. This occurs primarily because weeds use resources that would otherwise be available to the crop. The magnitude of yield loss is affected by numerous agronomic and environmental factors, most importantly, weed density and time of emergence relative to the crop. Practices that (1) reduce the density of weeds, (2) maximise occupation of space or uptake of resources by the crop or (3) establish an early‐seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
0
14
0
2
Order By: Relevance
“…Plant-plant interactions can be both positive (facilitation) and negative (competition). In most plant communities, the latter dominate, reducing individual plant growth, including root growth, and although positive effects can also be important in some situations (Gallandt and Weiner, 2015), competition among plants is one of the major determinants of plant community structure and dynamics (Hortal et al, 2017). Neighboring plants can belong to the same or different species, referred to as intraand interspecific interactions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Plant-plant interactions can be both positive (facilitation) and negative (competition). In most plant communities, the latter dominate, reducing individual plant growth, including root growth, and although positive effects can also be important in some situations (Gallandt and Weiner, 2015), competition among plants is one of the major determinants of plant community structure and dynamics (Hortal et al, 2017). Neighboring plants can belong to the same or different species, referred to as intraand interspecific interactions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In cereals, their height and enhanced ability to compete for light are traits that confer great competitive ability (see Gallandt & Weiner ). Experiments with spring barley ( Hordeum vulgare L.) cultivars of contrasting competitiveness indicated that the genotypes with a strong competitive ability against weeds emerged earlier and had early stem extension, longer main shoots in the tillering stage and small leaf angles (Didon ).…”
Section: Discussionmentioning
confidence: 99%
“…In designing this investigation, it was recognised that weed competition with crop species is generally evaluated by growth and yield characteristics of the target plant, such as plant height, leaf area, tillering, vegetative biomass production and crop yield (Ziska & Dukes, 2011). It has also been shown that weeds negatively affect crops in many ways other than economic yield levels (Gallandt & Weiner, 2015).Work presented here specifically focuses on whether weed competition has an impact on wheat grain quality, a question which has been paid only minor attention in most previous studies. In this respect, there are three components of community assembly that are potentially relevant to crop-weed interactions: species richness/abundance, functional traits diversity and polygenetic diversity (Gibson, Young & Wood, 2017).…”
Section: Introductionmentioning
confidence: 99%